2019
DOI: 10.3390/electronics8111216
|View full text |Cite
|
Sign up to set email alerts
|

New “Full-Bridge Buck Inverter–DC Motor” System: Steady-State and Dynamic Analysis and Experimental Validation

Abstract: A mathematical model of a new "full-bridge Buck inverter-DC motor" system is developed and experimentally validated. First, using circuit theory and the mathematical model of a DC motor, the dynamic behavior of the system under study is deduced. Later, the steady-state, stability, controllability, and flatness properties of the deduced model are described. The flatness property, associated with the mathematical model, is then exploited so that all system variables and the input can be differentially parameteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…4-7) it is concluded that the sensorless passivity-based control, for the angular velocity trajectory tracking task, in the full-bridge Buck inverter-DC motor system achieves the objective, i.e., ω → ω * . Until now, the only experimental work related to the fullbridge Buck inverter-DC motor system, is the one where its mathematical model was developed and experimentally validated [59]. In the experimental tests reported in [59] the four desired trajectories ω * used there were the same ones used in this paper, i.e., ( 25)- (28).…”
Section: Comments On the Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4-7) it is concluded that the sensorless passivity-based control, for the angular velocity trajectory tracking task, in the full-bridge Buck inverter-DC motor system achieves the objective, i.e., ω → ω * . Until now, the only experimental work related to the fullbridge Buck inverter-DC motor system, is the one where its mathematical model was developed and experimentally validated [59]. In the experimental tests reported in [59] the four desired trajectories ω * used there were the same ones used in this paper, i.e., ( 25)- (28).…”
Section: Comments On the Experimental Resultsmentioning
confidence: 99%
“…An application recently developed that uses such a system can be found in [34], where the problem of renewable energy power source based on fuel cells was presented by Chi et al in 2020. Motivated by the benefits of the new "full-bridge Buck inverter-DC motor" system [59]:…”
Section: Discussion Of Related Work Motivation and Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the PWM techniques for five-level inverter are presented in [14,15], with a minimal number of commutations. The inverter topology for the DC motor is presented in [16].…”
Section: The Current Research Trendsmentioning
confidence: 99%